2018
DOI: 10.1371/journal.pone.0190671
|View full text |Cite
|
Sign up to set email alerts
|

Public opinion towards castration without anaesthesia and lack of access to pasture in beef cattle production

Abstract: Recent publications have shown that citizens in developing nations are gaining interest in farm animal welfare. The aims of this study were to assess the opinion of Chilean citizens about surgical castration without anaesthesia and lack of access to pasture in beef cattle production, to investigate how involvement in livestock production influences opinions, and to evaluate if different types of information would affect their opinion towards these management practices. The study was carried out in the Metropol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 48 publications
3
23
0
Order By: Relevance
“…In comparison with choice methodologies, where researchers choose topics on which participants will give their opinion [ 29 , 32 , 47 ], this methodology avoids soliciting participants’ opinion on issues they may have little or no understanding. We considered that relevant, given several reports of low awareness towards animal production systems and animal welfare among citizens in Latin America [ 5 , 23 , 60 ]. Social desirability bias (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with choice methodologies, where researchers choose topics on which participants will give their opinion [ 29 , 32 , 47 ], this methodology avoids soliciting participants’ opinion on issues they may have little or no understanding. We considered that relevant, given several reports of low awareness towards animal production systems and animal welfare among citizens in Latin America [ 5 , 23 , 60 ]. Social desirability bias (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The only demographic characteristic of participants that influenced attitudes towards piglets’ castration was sex, with women showing more negative attitudes towards surgical castration in both surveys, as shown in two previous studies [ 33 , 57 ], and adding to several others that have shown that women have greater concerns regarding farm animal welfare [ 52 ]. More than 25% of the participants in both samples reported growing up with some contact with farm animal production.…”
Section: Discussionmentioning
confidence: 61%
“…However, meat-eating habits had some influence on acceptability of surgical castration and its alternatives. As shown in a Chilean study [ 57 ], acceptability of surgical castration tended to be greater among participants that ate meat more frequently and those that considered meat more important. This finding is relevant because more than half of the participants in both samples rated eating meat as important, and over three quarters ate meat 3 to 7 days a week.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations